Bioethical issues of tissue engineering and regenerative medicine: a preliminary review from Islamic perspective - Abdul Rahman, Rozlin; Sulaiman, Norhayati Aida; Hashi, Abdurezak Abdulahi; Mohamad Rashidi, Norhafizah; Sha'ban, Munirah (Revelation and Science, IIUM, 2014)
Modern advances in biochemistry, cell and molecular biology, genetics, biomedical engineering and material sciences, have contributed to the development of tissue engineering and regenerative medicine (TERM). Although TERM is still in its initial phases, significant breakthrough in this cross- disciplinary area has clearly marked the way for the establishment of a promising new biomedicine technology which actively seeks to reconstruct tissues/organs or spare parts for the human body to repair, restore or replace damaged tissues. However, these breakthroughs have raised number of moral and legal questions, including among others, is it moral to genetically modify the human genes? What are the moral and legal implications of regenerative medicine? Does organ reconstruction or tissue replacement activity violate basic religious beliefs or legal status of the person? Through textual and analytical methods, this paper aims to explore relevant concerns from t he Islamic perspective. Besides the texts of the Qur’an and the Prophetic narrations (hadith), both Muslim jurists (fuqaha) and ethicists’ opinion on these matters would be unveiled.